2018
DOI: 10.1155/2018/8576890
|View full text |Cite
|
Sign up to set email alerts
|

Shiftwork-Mediated Disruptions of Circadian Rhythms and Sleep Homeostasis Cause Serious Health Problems

Abstract: Shiftwork became common during the last few decades with the growing demands of human life. Despite the social inactivity and irregularity in habits, working in continuous irregular shifts causes serious health issues including sleep disorders, psychiatric disorders, cancer, and metabolic disorders. These health problems arise due to the disruption in circadian clock system, which is associated with alterations in genetic expressions. Alteration in clock controlling genes further affects genes linked with diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 118 publications
(150 reference statements)
0
67
1
4
Order By: Relevance
“…Many of past studies have agreed that disruption of the circadian system is seen as relevant for shift workers, putting them at a major risk to be affected by health impairment. A recent review done by Khan et al (2018) reported that despite the social inactivity and irregularity in habits, working in continuous irregular shifts causes serious health issues including sleep disorders, psychiatric disorders, cancer, and metabolic disorders.…”
Section: Circadian Disruption Among Shift Workersmentioning
confidence: 99%
“…Many of past studies have agreed that disruption of the circadian system is seen as relevant for shift workers, putting them at a major risk to be affected by health impairment. A recent review done by Khan et al (2018) reported that despite the social inactivity and irregularity in habits, working in continuous irregular shifts causes serious health issues including sleep disorders, psychiatric disorders, cancer, and metabolic disorders.…”
Section: Circadian Disruption Among Shift Workersmentioning
confidence: 99%
“…In recent years, people's sleep time has shown a downward trend. The average daily sleep time of Chinese residents is 7.20 h, and the proportion of people with sleep insufficiency is 23.60% (47). Similarly, the proportion of young Americans who sleep for less than 7 hours/day has risen from 15.6% to 37.1% in the last 40 years (48).…”
Section: Sleep-related Factorsmentioning
confidence: 99%
“…Surprisingly, Per1 and Per2 behave differently during phase shifts (jet lag or shiftwork) 6 , 25 that may ultimately cause the disruption in the circadian clock. Along with sleep regulation, circadian rhythms also direct normal physiological processes, including hormone secretion, body temperature, feeding behavior, cell-cycle progression and drug, glucose and xenobiotic metabolism 10 , 22 .…”
Section: Circadian Systemmentioning
confidence: 99%
“…Long-term exposure to irregular dark-light cycles increases the risk of sleep disorders, metabolic disorders, mental abnormalities, depressive disorders, and hormonal abnormalities, that further develop cancer, gastrointestinal, and reproductive disorders 10 . Trans meridian travel may develop general malaise, headaches, insomnia, daytime sleepiness, impaired cognitive or physical performance and gastrointestinal disturbances.…”
Section: Introductionmentioning
confidence: 99%